Pengaruh disiplin terhadap produktivitas kerja karyawan pada Surya Toserba Kadipaten Kabupaten Majalengka - Syari, Irna; Eli Dahlia (Program Studi Akuntansi IKOPIN, 2022)
The purpose of this research is to obtain data and information needed to be processed, analyzed, and interpreted, regarding the analysis of work discipline its impact on employee productivity at Surya Toserba Kadipaten Majalengka Regency, so that it can be used as a research proposal in fulfilling one of the requirements of a research proposal program. Management studies at the College of Economics (STIE) STMY Majalengka. The method of data collection in this study was a questionnaire filled out by respondents, namely employees of Surya Toserba Kadipaten Majalengka Regency. The sampling of 55 respondents in this study used the incidental sampling method. The analysis used in this research includes analysis of validity test, reliability test, linear regression analysis, correlation analysis and coefficient of determination, hypothesis testing t-test. There is a positive and significant influence between work discipline on employee work productivity at Surya Toserba Kadipaten Majalengka Regency. Because the value of tcount is greater than ttable (10.0098 > 1.66123) so H0 is rejected. the coefficient of determination for discipline on the work productivity of Surya Toserba Kadipaten Majalengka employees is 51.60%. The influence of other factors is equal to (100%−51.60%) = 48.40%. This influence is the influence of other factors outside of the discipline variable on work productivity. The result of calculating the correlation value between discipline and work productivity of Surya Toserba Kadipaten Majalengka Regency employees based on research data obtained is 0.7183, then the relationship between work discipline variables and work productivity of Surya Toserba Kadipaten Majalengka Regency employees are included in the strong group. The results of the calculation of the regression coefficients based on the research data obtained can be written in the estimated regression equation as follows: Y = 9.11 + 0.35 X.